Investigating Digital Storytelling as a Tool of Improving/ Developing Information Literacy Skills - Maryam Khodabin; Mohammad Zerehsaz; Somaye Sadat Akhshik; Ghasem Azadi Ahmadabadi (کتابداری و اطلاع‌رسانی)
Objective: Digital storytelling is an innovative tool and works as a promising activity to facilitate and develop learning in the postmodern society. Digital storytelling emphasizes the group process and people's experience in sharing stories, visual and verbal functions that are necessary for understanding language and thinking from the perspective of cognitive neuroscience. It also provides an interactive approach to create a learning group, engage learners in digital literacy and create educational opportunities for global interaction with audiences and can play an important role in expanding people's digital literacy. Therefore, as a modern tool, it can play an important role in the development of people's information literacy. This research was conducted with the aim of investigating the use of digital storytelling in expanding information literacy.Methodology: The current research was done with a qualitative approach and through content analysis. In order to obtain comprehensive information, all valid domestic and foreign scientific articles related to the research topic in the period of 2000-2024 were selected as the research community, and 53 articles were selected using targeted sampling. The search was performed in Google Scholar and specialized databases such as Medline, SID, Magiran, Pubmed, Scopus, and ScienceDirect. Key terms such as digital storytelling, information literacy, storytelling education, impact of digital storytelling, e-learning, new learning alone and combined were used to find articles. The entry criteria included the validity of the sources, their accessibility and the year of their publication in the desired time period. Data collection was done through reading articles until saturation was reached.Findings: First, 53 basic themes were extracted from the texts. Then, the themes were divided into larger groups and identified as constructive themes. In the following, 14 constructive themes (verbal-linguistic skills, social skills, expansion of digital literacy, expansion of traditional literacy, collaborative learning, remembering content, organizing information, psychological capital, excitement, adaptability, intercultural communication, factors affecting the use of storytelling, attractiveness, Expansion of creativity) and finally 7 main themes (learning-remembering, verbal-social, psychological skills, individual-cultural adaptability, creativity, expanding literacy and causal factors) were identified.Conclusion: From this research, it can be concluded that digital storytelling has different advantages that can affect people's literacy in digital and non-digital fields. Digital storytelling as an educational and communication tool can have a great impact on expanding people's information literacy. Digital stories usually contain various information and knowledge conveyed to people through storytelling. This information can be transferred through stories in an attractive and understandable way for people and increase their knowledge and awareness.